PENGARUH PENGALAMAN KERJA, GENDER DAN PENGETAHUAN MENDETEKSI FRAUD TERHADAP AUDIT JUDGMENT - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
According to the results of research that has been conducted in KAP East Jakarta are 1. Work experience, gender, and knowledge of detecting fraud have a positive effect on audit judgment because the auditor in conducting audit judgment is seen from experience that matches the criteria and must be professional. 2. The auditor's experience has a positive influence on audit judgment because an experienced auditor will be able to hone sensitivity in information, fraud and misstatement of financial statements, which are related to making Judgment, the experience an auditor has by making the auditor learn from past mistakes in order to be able make better judgment. 3. Based on research that has been done shows that gender has no effect on audit judgment. This means that if gender is increasingly dominated it will not affect the level of understanding of audit judgment. 4. Based on research saying that the knowledge of detecting fraud has a significant effect on audit judgment, which means that the greater the knowledge of an auditor in detecting fraud, then an auditor will make it easier for auditors to examine financial statements.